Beyond total mesorectal excision in locally advanced rectal cancer with organ or pelvic side-wall involvement. Issue 8 (August 2018) - Mariathasan, A.B.; Boye, K.; Giercksky, K.E.; Brennhovd, B.; Gullestad, H.P.; Emblemsvåg, H.L.; Grøholt, K.K.; Dueland, S.; Flatmark, K.; Larsen, S.G.
Abstract: Background: In locally advanced rectal cancer (LARC), beyond total mesorectal excision (bTME) is often necessary to obtain complete resection (R0). The aim of this study was to identify prognostic determinants and compare morbidity and survival in LARC cases requiring bTME or TME surgery. Method: Single centre cohort study of LARC cases where all patients received neoadjuvant radiotherapy (n = 332). Data was registered prospectively in an institutional database linked to the National Registry. Results: bTME surgery was performed in 224 patients, 171 with resections of adjacent organs (bTME-o group) and 53 with pelvic side-wall resections (bTME-pw group). TME surgery was performed in 108 patients. Six deaths occurred within 100 days and severe morbidity was registered in 23.8% of the whole cohort and in 25.4% of the bTME groups. The R0 rates were 93.5%, 84.2%, and 75.5% in the TME, bTME-o, and bTME-pw groups, respectively. Five-year disease free survival (DFS) was 67.3% (TME group), 54.5% (bTME-o group) and 48.7% (bTME-pw group), and five-year overall survival (OS) 78.7%, 69.0% and 60.4% respectively. Patients with involved resection margins (R1), high pT-stage, pN-positivity or poor response to neoadjuvant therapy were associated with inferior DFS and OS. Conclusion: In organ-threatening or infiltrating LARC, bTME surgery can be performed with low mortality and acceptable morbidity to obtain a good long-term outcome. Patients with pelvic side-wall infiltration were identified as a subgroup with increased risk of R1 resection and inferior long-term outcome.